Process-Oriented Tolerancing for Additive Manufacturing—Application to Non-assembly Mechanisms - Schächtl, Paul; Schleich, Benjamin; Wartzack, Sandro (Research in Tolerancing, 2024)
Additive manufacturing (AM) is characterized by great design freedom and batch size-independent manufacturing costs, and also offers the possibility of manufacturing moving mechanisms in a single manufacturing step. A subsequent assembly step thus becomes obsolete, consequently leading to a considerable cost reduction. However, AM processes have the disadvantage that lower geometrical accuracy can be achieved compared to conventional manufacturing processes. Part quality is mostly technology- and machine-dependent and there is a lack of reliable and comprehensive information on the relationship between product and process design and achievable tolerances. These characteristics from process design must be considered in the design phase to ensure functionality. Existing approaches for virtual assurance of mechanism operability only deal with conventional manufacturing processes. The central objective of this contribution is to propose a framework for AM process-oriented tolerancing and the specific application for the virtual validation of the motion behavior of non-assembly mechanisms by means of statistical tolerance analysis. Through the deployment of the proposed framework, an analysis of these products prior to manufacturing can be achieved, thus leading to lower failure rates. The results from this analysis are therefore intended to serve as a basis for decision-making within product and process design for AM-inexperienced designer